2021
DOI: 10.1051/sicotj/2021004
|View full text |Cite
|
Sign up to set email alerts
|

Subacromial impingement by a lipoma arborescens

Abstract: Subacromial impingement syndrome (SIS) is the leading cause of shoulder pain. A systemic approach for abnormal causes of SIS is recommended to avoid misdiagnosing rare or sinister pathologies. To our knowledge, only nine cases of subacromial lipoma arborescens associated with impingement syndrome have been reported in the literature. In this report, we briefly discuss histopathologic and radiological signs of an unusual case of impingement syndrome caused by subacromial “lipoma arborescens” and describe arthro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(35 reference statements)
1
1
0
Order By: Relevance
“…A systematic review on the arthroscopic treatment of LA of the knee revealed a satisfactory short-term outcome [ 15 ]. The present study supports similar findings: patients may benefit from less invasive arthroscopic procedures when feasible, as arthroscopic treatment of shoulder [ 2 , 3 , 28 , 35 , 36 ] and elbow lesions [ 13 ] led to promising short-term outcomes. Although LA was recognized as a clinical entity decades ago, the evidence is scarce and long term outcome data are unavailable.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A systematic review on the arthroscopic treatment of LA of the knee revealed a satisfactory short-term outcome [ 15 ]. The present study supports similar findings: patients may benefit from less invasive arthroscopic procedures when feasible, as arthroscopic treatment of shoulder [ 2 , 3 , 28 , 35 , 36 ] and elbow lesions [ 13 ] led to promising short-term outcomes. Although LA was recognized as a clinical entity decades ago, the evidence is scarce and long term outcome data are unavailable.…”
Section: Discussionsupporting
confidence: 90%
“…All patients had single lesion; one has a bilateral presentation [ 26 ]. Eleven lesions (50%) were located in the shoulder [ 1 3 , 22 , 24 , 28 , 30 , 32 , 33 , 35 , 36 ], seven (31.82%) in the elbow [ 13 , 23 , 25 , 26 , 29 , 34 ], and four (18.18%) in the wrist [ 14 , 27 , 31 , 37 ]. All patients but one had preoperative MRI scans during the diagnostic assessment [ 27 ].…”
Section: Resultsmentioning
confidence: 99%